Language and Conflict in Northern Ireland and Canada - Muller, J. author. aut Link
XIII, 281 p. 2 illus.
Keywords: In a unique contribution to understanding the interaction of language policy and planning in modern conflict resolution, Janet Muller provides an insider account of the search for improved status for the Irish language in Northern Ireland from the 1980s.